Drug prescription pattern in asthma in a tertiary care hospital in South India - Sethumadhavan, Sruthi; Parvathy, Kala Kesavan; Sulaiman, Shajahan Purathel (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Asthma, a chronic inflammatory disorder of the airways, affecting millions of individuals is a global health concern. It necessitates long-term management for optimal outcomes. impacting therapy costs and patient’s compliance. This study was done to analyse current prescribing trends in the management of asthma patients. This study examines current asthma treatment trends to enhance patient care and disease outcomes. Methods: This is an Observational cross-sectional study conducted at Government T. D. medical college, Alappuzha between October 2019 to September 2022. All patients clinically diagnosed with or a previously known case of asthma between 18-60 years of both sex attending the outpatient department of Pulmonary Medicine who gave consent for study were included. Data was collected by interviewing and from the patients OP card using a prestructured proforma. Data collected included patient details, allergy and smoking history, comorbid conditions, drugs prescribed for asthma along with dose, route and frequency of administration, concomitant medications, diagnostic tests if any. Results: Out of 200 asthma cases, 119 (59.5%) were females. The mean age was 43.95±10.62 years. 21 patients (10.5%) were smokers. 57 (28.5%) patients had an allergic predisposition. Hypertension n=48 (24%) was the most common comorbidity among the patients. A mean of 3.05±1.52 drugs per prescription. Out of 609 drugs prescribed, 450 (73.89%) drugs were from the National list of essential medicines (NLEM) and 366 (60.09%) drugs were from the WHO essential list. A combination of LABA with ICS was the most common drug given in 121 (60.5%) patients followed by Glucocorticoids 101 (50.5%) and PDE-inhibitor-Deriphylline 74 (37%) patients. Antibiotics was prescribed in 43 (21.5%) patients. 164 (82%) patients received a combination therapy. Out of the 609 drugs prescribed, 334 (54.8%) were oral followed by inhalational route 264 (43.3%). Conclusion: Study demonstrates the variability of drug utilization in asthma patients. The rising significance of PPMS (Prescription pattern monitoring studies) stems from heightened marketing of new medications, shifts in prescribing patterns and drug consumption, escalating worries regarding delayed adverse reactions, drug costs, and prescription volumes.